Review of Analytical Methods and Reporting of the Polyphenol Content of Tart Cherry Supplements in Human Supplementation Studies Investigating Health and Exercise Performance Effects: Recommendations for Good Practice - Sabou, Vlad R.; O'Leary, Mary F.; Liu, Ying; Brown, Paula N.; Murch, Susan; Bowtell, Joanna L. (Frontiers in Nutrition, 2021)
Tart cherries are a rich source of polyphenols that elicit antioxidant and anti-inflammatory effects. As a consequence, the effects of tart cherry derived supplements on markers of human health, exercise performance and sleep have been investigated. Supplementation protocols have been highly variable across studies and the dose of bioactive compounds used has often been poorly characterised. Specific and nonspecific analytical methods were employed for measuring the total polyphenol and anthocyanin content in tart cherry supplements. This review critically analyses the supplementation protocols and the analytical methods used for the characterisation of tart cherry supplements, culminating in recommendations for good practice in the analysis and reporting of the polyphenol content and profile of tart cherry products. A literature search was conducted using PubMed/Medline and Web of Science up to May 4th, 2020, including studies published in all years prior. Only articles written in English that provided a tart cherry dietary supplement as opposed to fresh whole tart cherry were included in this review. 43 studies were identified as eligible and included for analysis in this review. The studies investigated the effects of tart cherry supplementation on various aspects of human health, exercise recovery and performance and sleep. 20 studies conducted an analysis of tart cherry supplement and reported total polyphenol/anthocyanin content. 6 studies did not report the polyphenol content of the tart cherry supplement used. 17 studies reported the tart cherry supplement polyphenol content but this was derived from previously published studies and presumably different supplement batches. The duration of the supplementation protocol ranged from acute supplementation to 84 days, meanwhile the total polyphenol and anthocyanin dose ranged from 143 to 2140mg/day and 15 to 547mg/day, respectively. Due to the variety of specific and non-specific analytical methods used, the relative efficacy of different doses and polyphenol blends cannot reliably be extrapolated from critical analysis of the literature. Future studies should conduct an analysis of the study supplement batch. In addition to analysis and reporting of total polyphenol content, specific analytical methods such as HPLC UV/MS should be used to quantify total and individual anthocyanin contents.